Keselamatan Kesehatan Kerja Dan Pemberian Insentif Terhadap Kinerja Karyawan Pada PT.Putra Sinar Gas - Eloh Bahiroh; Ana Susi Mulyani (Sains: Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the effect of occupational safety healthy and incentives on employee performance at PT. Putra Sinar Gas. Sampling using saturatured sampling used 41 respondents, the data collection technique was through questionnaires and the research variables were occupational safety and healthy as a X1 , incentives (X2), and employee performance (Y). This study uses descriptive analysis with a quantitative approach and the data is processed by multiple linear regression analysis. Hypothesis testing using the F test and t test. From the results show that the value of correlation is 0.590 shows a moderate relationship between occupational safety and healthy and the incentive to employee performance. While the coefficient of determination of 0.348 means that the influence of occupational safety and healthy and the provisions of incentives on employee performce is 34,8%. The results of F test shows that there is a significant influence between occupational safety healthy and incentive on employee performance at PT. Putra Sinar Gas.